Clinical and morphological features of salmonellosis in cows and calves affected by heat stress - L. I. Drozdova; E. N. Shilova; I. A. Shkuratova; M. V. Ryaposova (Ветеринария сегодня)
Exposure to abnormally high temperatures in the Middle Urals has ledtochronic heat stress in cattle. Despitethe measures taken toprotect thedairy herdfrom overheating (fans, irrigationwith coolwater, livestocksunshades), the heatstressunderminedtheimmunityofanimals, thus, leadingtoan excessiverisein Salmonella population in the gastrointestinal tract, increasedin test in alpermeability, and could also bethecause of increasedvirulence of such serotypes as – Salmonella choleraesuis, that are not typical for cattle. The simultaneous presenceof twopathogensof Salmonella entericasubsp. entericaspecies: i.e. Salmonella enteritidis and Salmonella choleraesuis – causeda number of clinical and morphological changesin adultcows. In cows, the infection manifested itself by persistent diarrhea with mucus, reduced milkproduction and intoxication. In calves, the disease was accompanied by septic signs, severein toxication, hyperthermia (40.5–41.0 °C), severed ehydration (morethan 7%) and death. Histopathological examination of bovineparenchymal organs revealed changes typical for salmonellos is pathological process: specific salmonella granulomas were foundin parenchymalorgans (liver, spleen). Some pathological processestypical for sepsiswere foundin other parenchymalorgans (kidneys, heart). The nature of pathological changes in dicates that there is as epticprocess that spreads both hematogenically and lymphogenically, and the structure of granulomas most likely indicates that such apathogen as Salmonelacholeraesuis circulates in cattle.